2011
DOI: 10.2337/dc11-1379
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Admission Glucose and Mortality in Patients With Acute Pulmonary Embolism

Abstract: OBJECTIVEAlthough associated with adverse outcomes in other cardiopulmonary conditions, the prognostic value of elevated glucose in patients with acute pulmonary embolism (PE) is unknown. We sought to examine the association between glucose levels and mortality and hospital readmission rates for patients with PE.RESEARCH DESIGN AND METHODSWe evaluated 13,621 patient discharges with a primary diagnosis of PE from 185 acute care hospitals in Pennsylvania (from January 2000 to November 2002). Admission glucose le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
3
26
1
Order By: Relevance
“…Furthermore, 30-day mortality increased with blood glucose levels. Interestingly, hyperglycemia has been reported as a prognostic factor for unfavorable short-term prognosis in patients admitted to the intensive care unit for pulmonary embolism [23] as well as for other diseases, including myocardial infarction, arrhythmia, unstable angina, heart failure, stroke, gastrointestinal bleeding, pneumonia, renal failure, and sepsis [24]. However, no conclusions regarding whether strict control of blood glucose levels improves prognoses for intensive care unit patients have been made [24].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, 30-day mortality increased with blood glucose levels. Interestingly, hyperglycemia has been reported as a prognostic factor for unfavorable short-term prognosis in patients admitted to the intensive care unit for pulmonary embolism [23] as well as for other diseases, including myocardial infarction, arrhythmia, unstable angina, heart failure, stroke, gastrointestinal bleeding, pneumonia, renal failure, and sepsis [24]. However, no conclusions regarding whether strict control of blood glucose levels improves prognoses for intensive care unit patients have been made [24].…”
Section: Discussionmentioning
confidence: 97%
“…Hyperglycaemia has been associated with a number of adverse outcomes in certain hospital populations, including patients with acute myocardial infarction, community‐acquired pneumonia, stroke, chronic obstructive pulmonary disease (COPD), trauma and pulmonary embolism . The effects of glycaemic control on clinical outcomes have been examined extensively in patients during critical illness .…”
Section: Introductionmentioning
confidence: 99%
“…Movahed et al reported that 0.7% of patients with diabetes suffered pulmonary embolism, whereas only 0.5% of the controls suffered pulmonary embolism (odds ratio, 1.27; 95% confidence interval, 1.19-1.35; P < 0.001) [28]. In addition, a large retrospective cohort study showed that elevated glucose levels were present in the majority of patients with acute pulmonary embolism and were independently associated with 30-day mortality [29]. The reason for the close connection between diabetes mellitus and pulmonary embolism is that hyperglycaemia contributes to coagulation activation and hypofibrinolysis, resulting in a prothrombotic state [30].…”
Section: Discussionmentioning
confidence: 96%